Entrepreneurial Specific Factors, Support Factors and Micro enterprises Performance: The Case of Malaysian Microcredit Program - Ibrahim, Norlaila; Mahmood, Rosman; Mohd Zahari, Ahmad Suffian; Mulyana, Mulyana (Information Management and Business Review, 2024)
The study’s objective is to analyze the influence of several elements related to entrepreneurial-specific factors and support factors on the performance of micro-enterprises. The study sample consisted of a total of 756 micro-entrepreneurs who were involved in two main microcredit programs in Malaysia, namely Amanah Ikhtiar Malaysia (AIM) and The Venture Group Economic Fund (TEKUN). The study’s findings, obtained through multiple regression analysis, revealed that factors such as personal entrepreneurial competencies, management practice, microcredit programs and government support exert a significant influence on the performance of micro-enterprises. This finding is consistent with the Resource Base View (RBV) theory which links the importance of internal and external resources as a catalyst for competitive advantage and the performance of a business. The influence of family and commitment to religious principles is less significant. It was associated with the attitude factor of micro-entrepreneurs, who frequently disregard the fundamental principles of religion while making judgments. The impact of family influence on micro enterprises’ performance was determined to be negligible. Family members make minimal contributions in terms of finances, energy, or moral support. The formulation of policies is crucial for these insights, which highlight the importance of providing entrepreneurship training and implementing excellent management practices. Additionally, financial support is necessary to promote the growth of micro-enterprises in Malaysia. The government plays a crucial role in facilitating the growth of micro companies by implementing various support programs. An efficient distribution system can minimize the leakage of programs and maximize benefits for the recipients who are intended.